Design of chord sidewall failure in RHS joints using steel grades up to S960 - Lan, Xiaoyi (2022)
It is well known that the current design rules adopted by international design codes such as ISO 14346 and design guides, e.g., the CIDECT design guide No. 3, for chord sidewall failure in mild steel rectangular hollow section (RHS) joints under brace axial compression are considerably conservative, if the RHS joints are adequately supported out-of-plane. This paper presents an investigation into chord sidewall failure in RHS joints using steel grades up to S960. Representative existing design methods for chord sidewall failure in RHS joints are reviewed, and two alternative design methods, i.e., the modified bearing–buckling method and the Lan–Kuhn​ method, are proposed. Up-to-date test and numerical results reported in the literature are compiled. A wide range of geometric parameters, steel grades up to S960 and loading cases of brace axial loading, brace in-plane bending and brace out-of-plane bending are covered. The existing and proposed design methods are assessed against the collated results. The effects of brace-to-chord height ratio, brace angle, steel grade and chord stress ratio are evaluated. It is shown that the proposed design methods can provide more consistent resistance predictions for chord sidewall failure in mild steel and high-strength steel RHS joints under brace axial compression. Corresponding user-friendly design rules are suggested. The design of chord sidewall failure in RHS joints under brace axial tension, brace in-plane bending and brace out-of-plane bending is discussed. Further required research on, in particular, high-strength steel RHS joints is highlighted.